2023
DOI: 10.1186/s40001-022-00963-x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and effects of cognitive–motor exergames on fall risk factors in typical and atypical Parkinson’s inpatients: a randomized controlled pilot study

Abstract: Background People with Parkinson`s disease (PD) often suffer from both motor and cognitive impairments. Simultaneous motor and cognitive training stimulates neurobiological processes which are important especially for people with PD. The aim of this study is to test the feasibility and effects of simultaneous cognitive–motor training in form of exergames in the setting of inpatient rehabilitation of persons with PD. Methods Forty participants (72.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 70 publications
1
28
0
Order By: Relevance
“…Acceptance was associated with exergame being enjoyable, easy-to-use, and motivational [14]. Low attrition was observed in an RCTs which was associated with easy-to-use characteristic of the exergame [19]. The adherence rate was high as reported in three studies [14,19,27], where some studies reported the adherence rate of 97% [19] and 80% [27]…”
Section: Acceptance and Adherencementioning
confidence: 85%
See 4 more Smart Citations
“…Acceptance was associated with exergame being enjoyable, easy-to-use, and motivational [14]. Low attrition was observed in an RCTs which was associated with easy-to-use characteristic of the exergame [19]. The adherence rate was high as reported in three studies [14,19,27], where some studies reported the adherence rate of 97% [19] and 80% [27]…”
Section: Acceptance and Adherencementioning
confidence: 85%
“…In this present systematic review, fourteen studies assessing the QoL were included. Twelve of which reporting about Parkinson's disease and the other two -Alzheimer's disease [14,15,[24][25][26][27][28][16][17][18][19][20][21][22][23]. Most of Parkinson's disease studies used PDQ-39 and EQ-5D.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations